Determination of wear elements in steyr ursus tractor lubricating oil using atomic absorption spectroscopy (AAS) - Ahmad, Habib Imam; Suleiman, M. L.; Ahmad, Desa; Yusuf, D. D. (Faculty of Engineering, Universiti Putra Malaysia, 2012)
A study was conducted to determine the presence and level of wear elements in engine lubricating oil of steyr ursus tractors. Ten tractors engaged in refuse collection and disposal within Kano metropolitan area were selected and their engine oils samples collected over a period of three months at intervals of one week. The oil samples were prepared for elemental determination using atomic absorption spectroscopy (AAS) by dry ashing and aquaregia solutions. Results indicated presence of eight elements (Zinc, Copper, manganese, Nickel, Copper, Cobalt, Lead and Chromium). Data was analysed using SAS package in completely randomized design with no replications. The ANOVA show significant differences between the tractors in element concentrations for Fe, Cu, Ni, Cr and Zn. However, using available concentration limits in the literature, chromium is the only element found exceeding tolerable limit. Chromium is an alloy constituent of engine parts principally concerned with engine power generation. The study recommends regular monitoring of wear elements in order to obtain satisfactory performance and avoid premature failure during critical period of operations.